Advances in Edible Oil Processing - Ferreira-Dias, Suzana; Xu, Xuebing; Peres, Fátima (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
During the last few decades, environmental concerns have prompted the food industry to find sustainable solutions in terms of the efficient use of natural resources and the development of eco-friendly processes and products, following the principles of a circular economy and biorefinery concepts. In the field of edible oil processing in particular, novel technologies have been developed to avoid the use of highly pollutant organic solvents and chemicals, high temperatures, and chemical catalysts as well as to produce novel lipids with improved functional and bioactive properties. In these novel products, the use of either traditional or non-traditional lipid sources from agro-wastes or by-product origins have been explored. These strategies meet consumers' concerns about what they eat and about the impact of their diet on their health and wellness. Therefore, this Special Issue comprises a collection of innovative research articles and review papers on advances in edible oil processing, including the following topics of interest: (1) Enzyme-catalyzed processes; (2) Emerging physical extraction techniques; (3) Green solvent extractions; (4) Innovative processes in olive oil extraction technology; (5) Contaminant mitigation technology; (6) Novel products.